PENINGKATAN KEMAMPUAN MENDENGARKAN INFORMASI BERITA PADA KELAS X B SMA PIRI 1 YOGYAKARTA DENGAN MENGGUNAKAN MEDIA AUDIO VISUAL - Danny Amar Burhanudin; Siti Rochmiyati (Universitas Sarjanawiyata Tamansiswa, 2017)
This study aimed to describe (1) the increase in student activity, and (2) an increase in the ability to listen to the news information using audiovisual media in class X B SMA PIRI 1 Yogyakarta. This study is a collaborative action research. The research subjects were 24 students, learning research object listen to audiovisual media. The method used in this research is observation, testing, and interview validity of the data with content validity and students’ interaction with students, students, and teachers, as well as the score. The results showed (1) students activity increased, their mean on prusiks 54,16%, 70,83% the first cycle and the second cycle to 83,33%. (2) the ability to listen to the new information that students increase their mean prasiklus 12,5%, 66,66% the first cycle, and became 91,66% in the second cycle.